Federal Republic of Yugoslavia - Breaking with the Past : The Path to Stability and Growth - World Bank (Washington, DC, 2013)
The study focuses on the renewed transition to democracy, and a market economy in the Federal Republic of Yugoslavia (FRY), within the context of extremely difficult economic, and social conditions: poor macroeconomic outcomes, with sharp drops in output, and trade, and, very high inflation; severe enterprise, financial, and infrastructure deterioration; and, worsened social indicators, showing increased poverty levels. Although the Federal authorities implemented reforms in foreign trade policy, initiated customs administration reforms, and developed a plan for bank restructuring, these early successes were still on the path of difficult reforms, and institutional strengthening. The Federal, and Republican Governments, will require the adoption of transition reforms, and investment priorities to meet three inter-dependent challenges: restoring macroeconomic stability, and external balance; stimulating growth, and creating the basis for a sustainable supply response; and, improving the social well-being of the most vulnerable, and building human capacity. The successful implementation of the reform program, institutional strengthening, and investments, will further require donor support, external debt reduction, financial support, and technical assistance, to restore economic growth, through fiscal adjustment, and a comprehensive debt restructuring. The study provides financing estimates for the period 2001-05 for structural adjustment, fast disbursing balance of payments, and budgetary support.